Dual‐Mode Organic Electrochemical Transistors Based on Self‐Doped Conjugated Polyelectrolytes for Reconfigurable Electronics (Adv. Mater. 23/2022). Issue 23 (9th June 2022) - Nguyen‐Dang, Tung; Chae, Sangmin; Chatsirisupachai, Jirat; Wakidi, Hiba; Promarak, Vinich; Visell, Yon; Nguyen, Thuc‐Quyen
Abstract : Organic Electrochemical Transistors A dual ionic transport property of self‐doped conjugated polyelectrolytes is reported by Thuc‐Quyen Nguyen and co‐workers in article number 2200274 : they can be both doped and dedoped upon the interaction with anions (blue) and cations (red) in an electrolyte, respectively. This discovery enables dual‐mode organic electrochemical transistors, paving the way for the use of organic devices in emerging reconfigurable electronics.